2021
DOI: 10.1177/23259671211035106
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasonography for Rotator Cuff Tears: A Systematic Review and Meta-analysis

Abstract: Background: With recent improvements in transducer strength, image resolution, and operator training, ultrasound (US) provides an excellent alternative imaging modality for the diagnosis of rotator cuff tears. Purpose: To evaluate the diagnostic accuracy of US for partial- and full-thickness rotator cuff tears and biceps tendon tears, compare diagnostic values with those of magnetic resonance imaging (MRI) using arthroscopy as the reference standard, assess longitudinal improvements in accuracy, and compare di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“…In the IT or OF type of injury, the measurement was performed at the thickest point of RC (follow-up estimated tendency for reduction of inflammatory and oedematous overgrowth of the RC as a sign of regeneration). It should be emphasised that ultrasound examination of the shoulder, especially RC thickness, which was performed according to the standards and based on the current state of the art, is highly sensitive and specific for the diagnosis of supraspinatus tears and presents equivalent capability to MRI in the diagnosis of both full- and partial-thickness RC tears (PT-RCTs) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the IT or OF type of injury, the measurement was performed at the thickest point of RC (follow-up estimated tendency for reduction of inflammatory and oedematous overgrowth of the RC as a sign of regeneration). It should be emphasised that ultrasound examination of the shoulder, especially RC thickness, which was performed according to the standards and based on the current state of the art, is highly sensitive and specific for the diagnosis of supraspinatus tears and presents equivalent capability to MRI in the diagnosis of both full- and partial-thickness RC tears (PT-RCTs) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, because arthroscopy involves an anaesthetic and a surgical procedure, it is not appropriate to be used as the first line of assessment 9 . Although MRI remains the preferred imaging modality for shoulder assessment, 1–3 USS is emerging as a cost‐effective, reliable, and convenient alternative due to continued improvement in transducer resolution and consistent education 24,26,27 . While the results of our research may impact on the diagnostic imaging choices prior to supraspinatus arthroscopy with USS being used as an alternative to MRI, our study suggests, practices should audit USS to see if these results concur generally.…”
Section: Discussionmentioning
confidence: 84%
“…Recent meta-analysis published in 2020 and 2021, 27,30 found good correlation between MRI and USS for FTT though a lower sensitivity for both modalities compared to arthroscope for characterising PTT. 27,30 These results appear to be broadly consistent with earlier systemic reviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography is among other imaging techniques for the diagnosis of subscapularis tendon disorders . Although there are numerous studies on the accuracy of ultrasonography for diagnosing rotator cuff tendon tears particularly supraspinatus tendon tears, there are limited studies on the accuracy of ultrasonography in diagnosing subscapularis tendon tears ( 32 ). A meta-analysis conducted by Farooqi et al on the diagnostic accuracy of ultrasonography for rotator cuff tears showed that ultrasonography has a more diagnostic accuracy for bicep tendon tears (93%) and supraspinatus tendon tears (83%) compared to subscapularis tendon tears (76%).…”
Section: Discussionmentioning
confidence: 99%